Cell death by apoptosis is a feature of the rheumatoid nodule. Issue 1 (1st January 2003) - Highton, J; Hessian, P A; Kean, A; Chin, M
Abstract : Objective: To examine the site and extent of apoptosis in the rheumatoid nodule and to determine whether this process make a significant contribution to the control of inflammation in the rheumatoid nodule as in other granulomas. Methods: Nine nodules and seven synovial membranes were examined by terminal deoxynucleotidyl transferase-mediated nick end labelling (TUNEL) in situ and a subset was further examined by DNA electrophoresis. The phenotype of apoptotic cells was identified using monoclonal antibodies and immunohistology. Results: Apoptosis occurred in all zones of the nodule and, except in one case, was not focused adjacent to the necrotic centre. Apoptosis occurred in 3.5 (4.5)% (mean (SD)) of cells in the nodule and 3.6 (3.1)% of cells in synovial membranes. Apoptosis was more common in nodule T cells (4.1 (2.9)%) than fibroblasts (1.0 (1.4)%), p = 0.01. Among macrophages 3.2 (4.7)% were apoptotic. Banding of DNA consistent with apoptosis was seen in two of three nodules examined. Conclusion: Apoptosis occurs at a low level in the nodule, similar to the synovial membrane. The results suggest that two modes of cell death occur in the nodule: apoptosis, which occurs throughout the nodule; and necrosis, which is concentrated near the necrotic centre. Apoptosis was more common in infiltrating inflammatory cells than in resident fibroblasts. These results are consistent with the proposal that apoptosis of infiltrating inflammatory cells is important in controlling accumulation of cells in the rheumatoid nodule as has been established in experimental granulomas.